Experimental investigation on in‐plane lateral stiffness and degree of ductility of composite PVC reinforced concrete walls. (2nd May 2021) - Far, Harry; Nejadi, Shami; Aghayarzadeh, Mehdi
Abstract: This study investigates the in‐plane lateral stiffness and ductility of composite PVC encased concrete walls subject to the lateral loads using pushover tests to determine lateral strength and ductility characteristics of composite PVC encased walls filled with plain concrete, macro‐synthetic fiber reinforced concrete (RC), and steel RC. Eighteen concrete wall specimens were cast and subjected to pushover test to determine the load‐deflection curves. Based on the capacity curves resulting from the pushover tests, the yield and maximum displacements and subsequently structural ductility and performance factors according to Australian Standard for seismic design of buildings have been determined. The determined parameters as well as the initial and effective lateral stiffness values measured from the load‐deflection curves for all three cases were compared and the final findings have been discussed. Based on the outcomes of this study, it has become apparent that the tested composite PVC encased macro‐synthetic fiber RC walls can exhibit superior performance in terms of ductility when compared to the unreinforced concrete specimens. In addition, the results indicated that the initial in‐plane lateral stiffness values of the tested composite PVC encased macro‐synthetic fiber RC walls increased by 25% compared to the tested walls filled with plain concrete. In order to enable structural designers to design composite PVC encased concrete walls, ductility factors for this type of walls have been extracted from the test results for the three mentioned cases and proposed for practical applications. It has been concluded that all the PVC encased concrete walls evaluated in this study can be categorized as fully ductile structures.